The Effect of Service Speed, Employee Integrity, and Employee Empathy on Service User Satisfaction at the Customs and Excise Supervision and Service Office (KPPBC) Middle Type Tanjung Perak Customs - Ramadhany Nugroho*; Erna Setijaningrum (Universitas Syiah Kuala, 2023)
This study aims to (1) determine whether the speed of customs services, employee integrity, and employee empathy simultaneously have a significant effect on service user satisfaction at the Tanjung Perak Customs Middle Type KPPBC; (2) find out which of the speed of customs service, employee integrity, and employee empathy partially have a dominant influence on service user satisfaction at the Tanjung Perak Medium Customs Type KPPBC. The research method used is the survey method. The primary data source in this study was in the form of questionnaire data on service users at the Customs and Excise Service Office of the Tanjung Perak Medium Type Customs. Methods of data collection through field research methods (Field Research Method), namely questionnaires and literature studies. The results of this study indicate that (1) simultaneously the independent variables consisting of Service Speed, Integrity and Empathy have a significant effect on service user satisfaction in the supervisory office and Tanjung Perak Customs and Excise Services Surabaya is acceptable; (2) partially the dominant influence on service user satisfaction is the Service Speed variable.